STUDY OF THE CONDITION OF WATER PIPELINES AND THE QUALITY OF DRINKING WATER IN THE WATER SUPPLY SYSTEM OF THE CITY OF NUKUS - Orazbaev Azamat Nasratdinovich; Qurbaniyazov Alisher Jalgashovich; Madiyarov Allayar Azatovich; Joldasbayev Miyratdiyn Sultamurat-uli (Galaxy International Interdisciplinary Research Journal, 2023)
The article is devoted to the study of the work of monitoring changes in the mineralization of the water of the Amu Darya River within the Karakalpak Republic. The operation of the water supply system is described in stages and analyzed.